Legal regulation of road safety in the Ukrainian SSR in the mid-1960s (Bulletin of Kharkiv National University of Internal Affairs, 2025)
In the 1960s, the problem of road safety in Ukraine acquired great social significance of state importance. This was due to a significant increase in the number of cars and motorcycles, that is, an increase in the intensity of traffic on the roads. This, in turn, led to an increase in the number of road accidents. The most common violations were violations of the rules of intersections, as well as violations of the rules of overtaking and maneuvering. It was during this period that uniform Rules for the entire state on streets and roads were adopted, a new standard “Road signs and indicators” came into force, as well as a single standard for a distinctive sign for vehicles participating in international traffic. The departments for regulating street traffic were finally liquidated, and their functions were transferred to the State Traffic Inspectorate. The introduction of indicator tubes to detect the degree of alcohol intoxication of drivers began, the first stationary traffic militia posts appeared, which were supposed to monitor compliance with traffic rules on country roads. The first examination devices appeared to assess the theoretical knowledge of candidates for driver’s licenses. For driving a car and motorcycle while intoxicated, a large number of drivers were deprived of the right to drive, but the most common punishment for violating traffic rules was a warning by composting tickets, materials for violations were sent to the consideration of labor collectives and comradely courts, and fines were levied on violators. The main areas of activity of the executive branch in ensuring road safety include the technical improvement of cars and the creation of conditions for their high-quality technical maintenance, road construction and improving the equipment of roads with traffic management means, improving the training of drivers, and promoting road safety.
Keywords: Ukraine; 1960s; Ministry of Public Order; militia; administrative activities; road safety.